PENGARUH KUALITAS, KOMPETENSI, DAN KOMITMEN KERJA DOSEN TERHADAP KEPUASAN MAHASISWA - Dominik Tulasi (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2019)
The purpose of this study was to examine the impact of effective independent variables on dependent variable which encompasses: Service quality, Competence and Commitment towards Students’ satisfaction at Muhammadiyah Business School Jakarta. This study exposed inductively the positive causal relationship between independent variables toward dependent variable to meet deductive requirement of empirical justification in the field. This study used survey method as a way of quantitative approach to prove theories that had been bounded in this research. Furthermore, the research finding concluded that Lecturers’ service quality, competence and commitment are the determinant factors of students’ satisfaction in perceiving teaching-learning process as the core value and substance of the subjects. Linked to F test showing independent variables effect on dependent variable at point Anova: 273.712, which has significant meaning simultaneously. The partial t test showing the result effect, job competence at point 0,540, which means it has positive effect; than job commitment showing point 0,492, means that variable has less effect on its dependent variable; and service quality at point 0,964, means ti has significant effect on student satisfaction. In short, the result of this finding will impact on the prospect candidate students to be a part of their favorite Campus.